Some Observations on the Breeding of Chitals (Axis axis) in the Deer Park of Navegaon National Park - Patil, S. H. (Indian Forester, 2017)
The paper describes observations about breeding of chital or spotted deer Axis axis at deer park in Navegaon National Park, (Dist. Gondia, Maharashtra) during 1970-90. The observations of 144 births indicates that chital breed only once in a year, mostly from November to February. The animal avoids breeding in peak summer i.e. May when the temperature soars to 42Â°C and also during rainy season i.e. June- September. The sex ratio of male to female was observed to be 1:1.